Gamified Project-Based Learning for Digital Hajj Training: A Systematic Literature Review on Procedural Understanding and Practical Skills - A. Zainal Abidin; Rusijono Rusijono; Andi Mariono (LP. Ma'arif Janggan Magetan, 2026)
This study aims to analyze the characteristics, approaches, and effectiveness of Gamified Project-Based Learning (GPBL), as well as examine its role in supporting the development of procedural understanding and practical skills in digital hajj training. The method used is Systematic Literature Review (SLR) with the PRISMA procedure on articles obtained from the Scopus database using keywords related to GPBL, procedural understanding, practical skills, and digital learning. Of the 115 articles identified, 14 articles met the inclusion criteria, namely Scopus indexed articles published in the 2020–2026 range and discussed the implementation of GPBL, procedural understanding, practical skills, or digital learning in the context of education. The results of the study show that GPBL has the characteristics of project-based active learning that is integrated with gamification so that it is able to increase student involvement, motivation, and learning outcomes. In addition, practice-based learning has been shown to strengthen procedural understanding through systematic and contextual learning experiences. Interactive digital media combined with gamification and project activities also support the development of practical skills more effectively. The main theoretical impact of the synthesis of 14 articles suggests that GPBL serves as a pedagogical framework that connects procedural understanding with practical skills through active, collaborative, and meaningful learning experiences. This study concludes that the integration of GPBL, procedural understanding, and digital learning is a potential approach in supporting the development of more effective digital hajj training.